Transgenic Cotton (Gossypium hirsutum L.) to Combat Weed Vagaries: Utility of an Apical Meristem-Targeted in planta Transformation Strategy to Introgress a Modified CP4-EPSPS Gene for Glyphosate Tolerance - Karthik, Kesiraju; Nandiganti, Muralimohan; Thangaraj, Arulprakash; Singh, Shweta; Mishra, Pragya; Rathinam, Maniraj; Sharma, Manju; Singh, Nagendra Kumar; Dash, Prasanta K.; Sreevathsa, Rohini (Frontiers in Plant Science, 2020)
Weeds burden plant growth as they compete for space, sunlight and soil nutrients leading to 25%-80% yield losses. Glyphosate (N-(phosphonomethyl)glycine) is a widely used broad spectrum non-selective herbicide that controls weeds by inhibiting 5-enolpyruvylshikimate-3-phospate synthase (EPSPS) enzyme and interfering with the shikimate biosynthesis pathway. Cotton (Gossypium hirsutum L.) is one of the most important commercial crops grown worldwide for its fibre. We have developed herbicide tolerant transgenic cotton (cv. P8-6) by introgression of a codon-optimized and modified EPSPS gene (CP4-EPSPS) possessing an N-terminal chloroplast targeting peptide from Petunia hybrida. Due to the recalcitrant nature of cotton, a genotype-independent non tissue culture-based apical meristem-targeted in planta transformation approach was used to develop transformants. Though in planta transformation methodologies are advantageous in developing large number of transgenic plants, effective screening strategies are essential for initial identification of transformants. In the present study the use of a two-level rigorous screening strategy identified 2.27% of T1 generation plants as tolerant to 800 mg/L and 1500 mg/L of commercially available glyphosate (Roundup). Precise molecular characterization revealed stable integration, expression and inheritance of CP4-EPSPS in advanced generations of the promising transgenic events. Further, superiority of selected transgenic plants in tolerating increasing levels of glyphosate (500 to 4000 mg/L) was ascertained through reduced accumulation of shikimate. This report is the first of its kind where cotton transformants tolerating high levels of glyphosate (upto 4000 mg/L) and accumulating low levels of shikimate have been identified. This study not only reiterated the genotype-independent nature of the transformation strategy but also reiterated the translational utility of the CP4-EPSPS gene in management of weeds.